Experiential learning as a tool for improving happiness in the classroom: an action research approach - Cerdá Suárez, Luis Manuel (12th International Technology, Education and Development Conference (INTED), 2021)
In the last decade, the adoption of virtual learning environments in institutions of Higher Education have undergone a great growth worldwide. As a consequence of this progress of virtual environments at universities, there are many theoretical and empirical studies focused on examining the impact of experiential learning and teaching on students' level of happiness in the classroom. In this paper, a wide spatial representation of cross-sectional nature was conducted at universities in, Chile, Mexico and Spain between March and November 2017, within the framework of an international research of teaching innovation supported by the Universidad Internacional de La Rioja, Spain. This study presents an original scale derived from the Spanish version of the Subjective Happiness Scale, which has previously shown good levels of internal consistency in a study with Spanish and Mexican university students. The total number of students in this experiment was 110 and the ultimate aim of this work is to explore the impact exerted by different combinations of experiential learning and teaching designs on happiness in the classroom, considering some skills and personal characteristics of the students.
Keywords: experiential learning; teaching; happiness; classroom; higher education; WOS(2)